Self-Care Mobile Application for South Korean Pregnant Women at Work: Development and Usability Study - Lee Y; Choi S; Jung H (Dove Medical Press, 2022)
Yaelim Lee,1,2 Soeun Choi,3 Heejae Jung4 1College of Nursing, Catholic University of Korea, Seoul, Republic of Korea; 2Redcross College of Nursing, Chung-Ang University, Seoul, Republic of Korea; 3Department of Nursing, Yeouido St. Mary's Hospital, Seoul, Republic of Korea; 4Department of Nursing, Seoul National University Hospital, Seoul, Republic of KoreaCorrespondence: Yaelim Lee, Department of Nursing, College of Nursing, The Catholic University of Korea, 222, Banpo-daero, Seocho-gu, Seoul, 06591, Republic of Korea, Tel +82-2-2258-8148, Fax +82-2-2258-8148, Email ylcaregiver@gmail.comBackground: Pregnant women at work often encounter barriers to participating in prenatal education or conducting appropriate self-care practices due to their working conditions.Purpose: We aimed at developing a mobile-based intervention application (SPWW) for Korean pregnant women at work and testing its usability and preliminary effects to enhance their self-care practices.Patients and Methods: The application was developed and tested with thirty-one pregnant women at work and thirteen women's healthcare providers. The instruments used in this study were a modified Health Practices in Pregnancy Questionnaire II and a System Usability Scale. Descriptive analyses and t-tests were performed using SPSS 25.0. The participants' open-ended answers were analyzed using ATLAS. ti 8.Results: We developed the application focusing on four self-care topics: healthy diet, physical activity, sufficient rest, and stress management. After using the application for two weeks, participants' levels of exercise (p = 0.006), adequate fluid intake (p = 0.002), and limiting daily caffeine intake (p = 0.048) significantly improved. In addition to good usability scores, the suggestions for improvement made by the participants included diversifying the educational materials and adding individually customizable functions to the application.Conclusion: The application developed in this study enhanced self-care practices of pregnant women at work and showed adequate levels of usability. We expect the developmental process and details of the application provided in this study to serve as a sample guide for future studies.Keywords: pregnancy, prenatal care, telemedicine, internet-based intervention, Asian